2003
DOI: 10.1046/j.1365-2559.2003.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid mesothelioma and its histological mimics: a comparative immunohistochemical study

Abstract: Mesothelioma shows decreased expression of epithelial and mesothelial epitopes in its sarcomatoid components. A wide immunophenotypic overlap exists among sarcomatoid mesotheliomas, sarcoma, and sarcomatoid carcinomas. Cytokeratin and calretinin have the most value in differentiating sarcomatoid mesothelioma from sarcoma. However, because sarcomatoid mesothelioma can occasionally be cytokeratin-negative, the distinction between it and sarcoma may become arbitrary. With the exception of smooth muscle actin, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 23 publications
1
90
2
1
Order By: Relevance
“…It is known that epithelioid and sarcomatoid mesotheliomas show different antigen expression, with many mesothelial markers being frequently negative in sarcomatoid subtype. [67][68][69][70][71][72][73] A recent gene expression profile analysis applied to a large series of pleural mesothelioma cell lines and tissue samples identified two mesothelioma subgroups. Although sarcomatoid and desmoplastic mesotheliomas belonged to a single group associated with poorer prognosis, epithelioid mesotheliomas were either included in the sarcomatoid/desmoplastic group or fell in a distinct subgroup with a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that epithelioid and sarcomatoid mesotheliomas show different antigen expression, with many mesothelial markers being frequently negative in sarcomatoid subtype. [67][68][69][70][71][72][73] A recent gene expression profile analysis applied to a large series of pleural mesothelioma cell lines and tissue samples identified two mesothelioma subgroups. Although sarcomatoid and desmoplastic mesotheliomas belonged to a single group associated with poorer prognosis, epithelioid mesotheliomas were either included in the sarcomatoid/desmoplastic group or fell in a distinct subgroup with a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…As with other currently used immunohistochemical markers of malignant mesothelioma, 21,22 D2-40 is limited by its performance in areas of sarcomatoid differentiation. In addition to the reduced frequency of positively staining tumor cells, the interpretation of D2-40 staining in areas of sarcomatoid growth is complicated by the loss of the characteristic membranous staining pattern seen in epithelioid mesotheliomas and the high level of background staining present in both benign reactive pleural tissue and desmoplastic tissue surrounding infiltrating tumor cells.…”
Section: D2-40 In Malignant Mesotheliomamentioning
confidence: 99%
“…Calretinin is expressed in both the cytoplasm and nucleus. According to the literature, its expression in malignant mesothelioma varies, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but most authors report frequent expression in epithelioid malignant mesothelioma, with only few studies reporting expression below 90%. Interestingly, calretinin expression has been described in a wide variety of cells, including steroid-producing cells of the testis and ovary, adipocytes, eccrine-glands, keratinizing thymic epithelial cells and numerous tumors, for example Merkel cell carcinoma, Leydig cell tumors of the testis, esthesioneuroblastoma, adenomas of the adrenal gland, small cell carcinoma of the lung and adenomatoid tumor.…”
mentioning
confidence: 99%
“…The few publications that have evaluated calretinin expression in the three most frequent types of malignant mesothelioma separately present data that diverge from 18 to 100% positivity in sarcomatoid malignant mesothelioma, and 8 to 100% in biphasic malignant mesothelioma. 5,7,15,[18][19][20]33 The D2-40 staining frequency is also controversial in sarcomatoid and biphasic malignant mesothelioma. Whereas Chu et al 23 reported staining in all types of malignant mesothelioma, Ordóñ ez 24 did not detect any D2-40 staining in either sarcomatoid malignant mesothelioma or sarcomatoid areas of biphasic malignant mesothelioma.…”
mentioning
confidence: 99%